Building Integrated Thermoelectric Air Conditioners—A Potentially Fully Environmentally Friendly Solution in Building Services. Issue 1 (11th November 2019) - Ma, Xiaoli; Zhao, Han; Zhao, Xudong; Li, Guiqiang; Shittu, Samson
The refrigerants used in conventional vapor-compression air conditioning systems have detrimental effects on the global environment. Phasing-down hydrofluorocarbon (HFC) refrigerants for HVAC equipment over the next 20 years has been proposed. A thermoelectric air conditioning system that directly converts electrical energy to thermal energy using a simple solid-state semiconductor device, has the advantages of environmentally friendly, no refrigerant, very compact, high reliability, no moving parts (except for small fans), and it can be easily integrated into the building structure. However, the existing thermoelectric air conditioning systems have the problem of low Coefficient of Performance (COP), which limits its applications for domestic air conditioning. With the development of the thermoelectric technologies, the above problem is prospected to be solved. The paper presents an overview of recent advances in thermoelectric materials, thermoelectric module design and thermoelectric heating and cooling system design which would provide the potential to greatly improve the COP of the thermoelectric air conditioner. In addition, utilizing the waste heat of the thermoelectric system for domestic applications to improve the overall COP of the system would be an ideal way to promote public adoption of the TE air conditioner, which is discussed in this paper. The paper also presents an overview of the existing building integrated thermoelectric air conditioning systems and proposes a novel building integrated thermoelectric system that integrates a thermoelectric heat pump unit into a double-skin ventilated facade to provide heating and cooling, heat recovery ventilation and domestic hot water or drying services for buildings, based on the thermoelectric waste heat utilization. Several building integration methods of the proposed system are presented.